Evaluating Strategies to Reduce Ruminal Protozoa and Their Impacts on Nutrient Utilization and Animal Performance in Ruminants – A Meta-Analysis - Dai, Xiaoxia; Faciola, Antonio P. (Frontiers in Microbiology, 2019)
Several studies have evaluated the effects of complete or partial ruminal protozoa (RP) suppression; however, to this date, no practical suppressant has been identified and used in large scale. This meta-analysis is the first to quantitatively evaluate the effectiveness of multiple strategies to either completely or partially eliminate RP. This study compared 66 peer-reviewed articles (Nstudy = 15 for complete and Nstudy = 51 for partial RP elimination) that used supplemental phytochemicals and lipids, published from 2000 to 2018, to reduce RP in vivo. Data were structed to allow a meta-analytical evaluation of differences in response to different treatments (complete RP elimination, phytochemcials, and lipids). Data were analyzed using PROC MIXED in SAS with random effect of experiment and weighted by the inverse of pooled variance squared. Compared to control, both complete and partial RP elimination had no effect on ruminal methanogens and bacteria. Supplemental phytochemicals and lipids reduced RP by 6.3% and by 12.2%, respectively. Compared to control, complete RP elimination reduced methane production by 18.3%, and supplemental phytochemicals and lipids reduced it by 17.9% and 16.7%, respectively. Compared to control, complete RP elimination increased molar proportion of acetate by 2.7% while reduced butyrate by 25.7%; supplemental phytochemicals and lipids reduced molar proportion of acetate by 2.0% and 1.6% while increased propionate by 5.4 % and 4.8%, respectively. Compared to control, complete RP elimination reduced total tract digestibility of OM by 3.8% and NDF by 9.9%; supplemental phytochemicals and lipids reduced total tract digestibility of DM by 14.3% and 3.7%, respectively. Supplemental lipids also reduced total tract digestibility of OM by 3.06% and DMI by 7.2%. The RP was positively correlated with methane production, NDF, total VFA, molar proportion of acetate, NH3-N, and DMI, while negatively correlated with pH and molar proportion of propionate. In conclusion, RP plays important roles on methanogenesis, fiber digestion, and ruminal bacterial protein turnover, regardless of diets, and partial RP elimination could be beneficial to ruminants in terms of nitrogen utilization, methanogenesis, and the environment, but supplemental lipids may have a negative effect on DMI and milk yield.